A VDAC1-Derived N-Terminal Peptide Inhibits Mutant SOD1-VDAC1 Interactions and Toxicity in the SOD1 Model of ALS - Shteinfer-Kuzmine, Anna; Argueti, Shirel; Gupta, Rajeev; Shvil, Neta; Abu-Hamad, Salah; Gropper, Yael; Hoeber, Jan; Magrì, Andrea; Messina, Angela; Kozlova, Elena N.; Shoshan-Barmatz, Varda; Israelson, Adrian (Frontiers in Cellular Neuroscience, 2019)
Mutations in superoxide dismutase (SOD1) are the second most common cause of familial amyotrophic lateral sclerosis (ALS), a progressive neurodegenerative disease characterized by the loss of motor neurons in the brain and spinal cord. SOD1 neurotoxicity has been attributed to aberrant accumulation of misfolded SOD1, which in its soluble form binds to intracellular organelles, such as mitochondria and ER, disrupting their functions. Here, we demonstrate that mutant SOD1 binds specifically to the N-terminal domain of the voltage-dependent anion channel (VDAC1), an outer mitochondrial membrane protein controlling cell energy, metabolic and survival pathways. Mutant SOD1G93A and SOD1G85R, but not wild type SOD1, directly interact with VDAC1 and reduce its channel conductance. No such interaction with N-terminal-truncated VDAC1 occurs. Moreover, a VDAC1-derived N-terminal peptide inhibited mutant SOD1-induced toxicity. Incubation of motor neuron-like NSC-34 cells expressing mutant SOD1 or mouse embryonic stem cell-derived motor neurons with different VDAC1 N-terminal peptides resulted in enhanced cell survival. Taken together, our results establish a direct link between mutant SOD1 toxicity and the VDAC1 N-terminal domain and suggest that VDAC1 N-terminal peptides targeting mutant SOD1 provide potential new therapeutic strategies for ALS.